2009
DOI: 10.1111/j.1439-0396.2008.00852.x
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal function and gut microflora of broiler chickens as influenced by cereal grains and microbial enzyme supplementation

Abstract: A study was conducted to investigate the effect of the key cereal grains and a microbial enzyme supplement on broiler chicken performance, gut microflora and intestinal function. Ingestion of the barley-based diet was associated with low 28-day body weight, decreased feed intake and high FCR. The supplemental enzyme increased feed intake and weight gain of the chickens on a wheat-based diet. The pH of the gizzard and caecal contents varied with the grain type. Enzyme supplementation reduced ileal viscosity, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
82
4
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(94 citation statements)
references
References 56 publications
5
82
4
2
Order By: Relevance
“…Moreover, diet and breed could be expected to affect the bacteria in the cecum (Shakouri et al, 2009;Stanley et al, 2012). To analyze the effect of variation by both factors on the difference between the microbiota in cecal content and cecal drop on the one hand and cecal content and fecal drop on the other hand, different mixed models were run.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, diet and breed could be expected to affect the bacteria in the cecum (Shakouri et al, 2009;Stanley et al, 2012). To analyze the effect of variation by both factors on the difference between the microbiota in cecal content and cecal drop on the one hand and cecal content and fecal drop on the other hand, different mixed models were run.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, the colonization of the intestines by beneficial bacteria has been shown to promote epithelial cell turnover (34), increase mucous production (26), upregulate expression of genes involved in several important intestinal functions (14), and help with reinforcement of the mucosal barrier, modulation of the immune system, and metabolism of nutrients by the host (46). Although studies conducted using either cultivation-based or molecular biology analyses have documented that the intestinal microbiota of mature broiler chickens is relatively stable (10,24,45), this microbiota is still dynamic and can be manipulated to a large extent (8,31,37).…”
mentioning
confidence: 99%
“…Shakouri et al (25) found that enzyme supplementation explained the increase in the number of total anaerobic bacteria, lactobacilli, and microbial growth. Birds' responses to enzymes depend mainly on dietary cereal quality and quantity.…”
Section: Microbial Populationmentioning
confidence: 99%